Viewpoint on Viññāṇa in Buddhist Texts and Ṛgveda of Brahmanism - Choosukhserm, Thanakorn (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2018)
The objectives of this article was to survey the basic viewpoint about Viññāṇa in Buddhist texts and Rigveda of Brahmanism because belief of Viññāṇa has appeared in two religions. From this survey, it was found that Viññāṇa in Buddhism has always the rising and falling state temporarily, not immortal and has two meanings: consciousness or enlightening the objects through the eye, ear, nose, tongue, body and mind and some state believed that it is in one’s body as living, when body was dead, Viññāṇa would go out of the body and float freely to find the a place to reborn. This Viññāṇa has lots of names such as Citta, Mano, Manas or Manindriya etc. But Viññāṇa in Ṛgveda in Brahmanism has different names called Prāṇa, Ātman, Manas etc. Viññāṇa on this viewpoint is in human beings’ bodies and all livings. It has the immortal state, not born, deathless, not changeable and functions to reborn on the influence of each one’s Kamma.